2017
DOI: 10.1002/jum.14262
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐Enhanced Ultrasound Differentiation Between Low‐ and High‐ Grade Bladder Urothelial Carcinoma and Correlation With Tumor Microvessel Density

Abstract: Contrast-enhanced ultrasound can be used to differentiate low from high-grade bladder urothelial carcinoma. The TIC parameters of CEUS reflect the MVD of bladder urothelial tumors and may be helpful for evaluating tumor angiogenesis, with implications for clinical diagnosis, treatment, and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
(59 reference statements)
1
21
0
Order By: Relevance
“…In this case, the quantitative analysis showed the TIC characterized by high signal intensity, rapid wash-in, and early wash-out. This is similar to the results of Guo et al [10], which displayed tumor with high-grade microvessel density, with high signal intensity and a fast wash-out. Therefore, CEUS, with TIC analysis, may be a useful non-invasive method in preoperatively evaluating the angiogenesis of bladder carcinoma.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this case, the quantitative analysis showed the TIC characterized by high signal intensity, rapid wash-in, and early wash-out. This is similar to the results of Guo et al [10], which displayed tumor with high-grade microvessel density, with high signal intensity and a fast wash-out. Therefore, CEUS, with TIC analysis, may be a useful non-invasive method in preoperatively evaluating the angiogenesis of bladder carcinoma.…”
Section: Discussionsupporting
confidence: 92%
“…Angiogenesis plays important role in the vascularization, growth, and metastasis of tumors. It is reported that a early wash-out enhancement pattern is common in arteriovenous fistulas as a result of angiogenesis, with a less distribution of tortuous vessels and interstitial oedema vessels related to a quick wash-out of contrast agent from the blood vessels [10]. In this case, the quantitative analysis showed the TIC characterized by high signal intensity, rapid wash-in, and early wash-out.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The intratumoral MVD in the bladder cancer tissue were measured by immunohistochemistry. 38,39 The 4-µm rat bladder tissue paraffin sections were deparaffinized, rehydrated, and treated with 3% hydrogen peroxide (H 2 O 2 ) to remove endogenous peroxidase. Then they were incubated with the primary anti-CD34 antibody (Abcam, Shanghai, China) overnight at 4°C.…”
Section: Immunohistochemical Assaymentioning
confidence: 99%
“…Contrast-enhanced ultrasound (CEUS) has been shown to be a practical method of detecting the features of tumor angiogenesis in many studies, some of which investigated the correlation between CEUS parameters and MVD or VEGF expression to assess tumor angiogenesis [18,19]. CEUS has the ability to gather micro-vascular information in various organs, which increases the accuracy of tumor diagnosis [17,[20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%